The Antibiotic Andrimid Produced by Vibrio coralliilyticus Increases Expression of Biosynthetic Gene Clusters and Antibiotic Production in Photobacterium galatheae - Buijs, Yannick; Isbrandt, Thomas; Zhang, Sheng-Da; Larsen, Thomas Ostenfeld; Gram, Lone (Frontiers in Microbiology, 2020)
The development and spread of multidrug resistant pathogens have reinforced the urgency to find novel natural products with antibiotic activity. In bacteria, orphan biosynthetic gene clusters (BGCs) far outnumber the BGCs for which chemistry is known, possibly because they are transcriptionally silent under laboratory conditions. A strategy to trigger the production of this biosynthetic potential is to challenge the microorganism with low concentrations of antibiotics, and by using a Burkholderia genetic reporter strain (Seyedsayamdost, Proc Natl Acad Sci 111:7266–7271), we found BGC unsilencing activity for the antimicrobial andrimid, produced by the marine bacterium Vibrio coralliilyticus. Next, we challenged another marine Vibrionaceae, Photobacterium galatheae, carrier of seven orphan BGCs with sub-inhibitory concentrations of andrimid. A combined approach of transcriptional and chemical measurements of andrimid-treated P. galatheae cultures revealed a 10-fold upregulation of an orphan BGC and, amongst others, a 1.6 - 2.2 fold upregulation of the gene encoding the core enzyme for biosynthesis of holomycin. Also, addition of andrimid caused an increase, based on UV-Vis peak area, of 4-fold in production of the antibiotic holomycin. Transcriptional measurements of stress response related genes in P. galatheae showed a co-occurrence of increased transcript levels of rpoS (general stress response) and andrimid induced holomycin overproduction, while in trimethoprim treated cultures attenuation of holomycin production coincided with a transcriptional increase of recA (SOS stress response). This study shows that using antimicrobial compounds as activators of secondary metabolism can be a useful strategy in eliciting biosynthetic gene clusters and facilitate natural product discovery. Potentially, such interactions could also have ecological relevant implications.